The dissolved uranium concentration and 234U/238U activity ratio in groundwaters from spas of southeastern Brazil - Bonotto, Daniel Marcos [UNESP] (2017)
This paper describes the natural radioactivity due to 238U and 234U in 75 water sources from spas located in 14 municipalities in São Paulo and Minas Gerais states, Brazil. These waters are extensively utilized for drinking in public places, bottling and bathing purposes, among other uses. The water samples were taken from springs and pumped tubular wells drilled into different aquifer systems in the Paraná and Southeastern Shield hydrogeological provinces. The measurements of alpha-emitting radionuclides were also accompanied by the monitoring of temperature, pH, Eh, electrical conductivity, dissolved gases (O2, CO2, H2S, radon, thoron) and major constituents. The dissolved U concentration data were lognormally distributed. The median and mean values corresponded to 0.02 and 0.09 μg/L, respectively. Significant relationships were found among the 234U/238U activity ratio (AR) of dissolved uranium, the total dissolved solids (TDS) and dissolved bicarbonate contents, and also between the AR and dissolution rate in the monitored sites. The logU versus AR diagram used for the hydrogeochemical prospecting of concealed U deposits indicated that the water sources were mainly from reduced environments. The possibility of using the reciprocal of the dissolved U concentration and AR data to determine mixing volumes of different groundwater masses was demonstrated. The highest dissolved U concentration (4.82 μg/L) was well below the maximum allowed by WHO.